Keupayaan Perundangan Dan Kemampuan Suruhanjaya Pencegahan Rasuah Malaysia (Sprm) Dalam Menangani Aktiviti Pengubahan Wang Haram - Mohd Amin, Shahrulnaim (2022)
Money laundering is a global threat as criminals turn to economic activity to protect criminal activity and expand their influence. The flow of illegal money flowing in the economic system can affect the sustainability of a country's development. Malaysia is no exception to the threat of money laundering. Therefore, this study has three objectives. First, to study the impact of money laundering on the development of Malaysia. Second, to explore the legal capabilities of the Anti-Money Laundering Act 2001 (AMLA) in dealing with money laundering crimes. Third, to analyse the MACC's capability to deal with money laundering crimes. This study is an evaluation research. Whereas, the research design is a qualitative study and the approach of the study is General Inductive Approach. Primary data were obtained through in-depth interviews using purposive sampling technique. A total of 13 interview informants were selected consisting of MACC officers, academicians, Deputy Public Prosecutor, executives of non-governmental organizations and financial instituitions with an interest in crime prevention in Malaysia. Focus Group Discussion (FGD) was also held involving 10 participants consisting of MACC officers. The data obtained were analysed using content analysis method. The first finding of this study shows that Malaysia receives positive impacts from the economic benefits when illegal money flows into the financial industry, capital markets and real estate industry. However, money laundering activities from syndicated crimes and political financing have negative impacts on Malaysia's development process. The second finding found that AMLA has the ability to deal with money laundering crimes.